2017
DOI: 10.1038/s41598-017-17665-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cell Line Based Orthotopic Xenograft Mouse Model That Recapitulates Human Hepatoblastoma

Abstract: Currently, preclinical testing of therapies for hepatoblastoma (HB) is limited to subcutaneous and intrasplenic xenograft models that do not recapitulate the hepatic tumors seen in patients. We hypothesized that injection of HB cell lines into the livers of mice would result in liver tumors that resemble their clinical counterparts. HepG2 and Huh-6 HB cell lines were injected, and tumor growth was monitored with bioluminescence imaging (BLI) and magnetic resonance imaging (MRI). Levels of human α-fetoprotein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Figure 1 demonstrates this technique of intrahepatic injection of human tumor cells that was used in this study, with the resulting tumors shown. These intrahepatic HB xenograft models recapitulated the key hallmarks of the disease including elevated serum AFP levels, large exophytic tumors with active blood supplies, and embryonal histological phenotypes with elevation of AFP, Glypican-3 (GPC3), and β-catenin proteins [19]. These models, especially the HepG2 model, also displayed a consistent gene expression profile similar to human HB tumors [19].…”
Section: Intrahepatic Cell Line-derived Xenograft Modelsmentioning
confidence: 69%
See 3 more Smart Citations
“…Figure 1 demonstrates this technique of intrahepatic injection of human tumor cells that was used in this study, with the resulting tumors shown. These intrahepatic HB xenograft models recapitulated the key hallmarks of the disease including elevated serum AFP levels, large exophytic tumors with active blood supplies, and embryonal histological phenotypes with elevation of AFP, Glypican-3 (GPC3), and β-catenin proteins [19]. These models, especially the HepG2 model, also displayed a consistent gene expression profile similar to human HB tumors [19].…”
Section: Intrahepatic Cell Line-derived Xenograft Modelsmentioning
confidence: 69%
“…These intrahepatic HB xenograft models recapitulated the key hallmarks of the disease including elevated serum AFP levels, large exophytic tumors with active blood supplies, and embryonal histological phenotypes with elevation of AFP, Glypican-3 (GPC3), and β-catenin proteins [19]. These models, especially the HepG2 model, also displayed a consistent gene expression profile similar to human HB tumors [19]. Noted in the study was the observation that gene expression of the Huh-6 cells was changed by growth in the murine liver and that this correlated with differences in histology [19].…”
Section: Intrahepatic Cell Line-derived Xenograft Modelsmentioning
confidence: 91%
See 2 more Smart Citations
“…The orthotopic mouse model of HCC can be established by the injection of HCC cells or the tumor tissues into the mouse liver, and the growth of tumors can be monitored using imaging techniques (24,32,33). The present study directly injected the HCC Hepa1-6 cell line into the left liver lobes of mice to generate internal liver tumors, and Small Animal Diagnostic Ultrasound was performed at early (7 or 8 days) and late (20–27 days) time points to confirm the presence of a tumor and for the assessment of tumor burden, respectively.…”
Section: Discussionmentioning
confidence: 99%